Epistemic (in)justice, social identity and the Black Box problem in patient care - Khan, Muneerah (University of the Witwatersrand, Johannesburg, 2024)
This research report draws on (for the first time) the moral norms arising from the nuanced accounts of epistemic (in)justice in the work of decolonial scholars, and social identity in the work of relational autonomists to defend the thesis that using AI in patient care in light of the Black Box problem is deeply problematic and is ethically impermissible. This does not necessarily doom AI since it may be used for other purposes within the healthcare system. The report highlights what needs to happen to align AI with the moral norms it draws on. Deeper thinking – from backgrounds other than decolonial scholarship and relational autonomy – about the impact of AI on the human experience needs to be done to appreciate any other barriers that may exist. Future studies can take up this task.
A research report Submitted in partial fulfillment of the requirements for the degree Master of Science in Medicine (Bioethics and Health Law) to the Faculty of Health Sciences, School of Clinical Medicine, University of Witwatersrand, Johannesburg 2024
Keywords: Black Box AI; Healthcare; Patient-centred care; Epistemic justice; Social identity; SDG-3: Good health and well-being